1992
DOI: 10.1039/ft9928803319
|View full text |Cite
|
Sign up to set email alerts
|

Pulse radiolysis study of concentrated phosphoric acid solutions

Abstract: In the pulse radiolysis of concentrated phosphoric acid solutions, the direct action of radiation on phosphoric acid gives rise to the phosphate radical. The yields of the phosphate radical and the hydroxyl radical are proportional, respectively, to the electron fractions of phosphoric acid and water, and can be quantified as G('0H + H2PO',) = 0.30fw + 0.33, pmol J-'. The forward and reverse rate constants of the equilibrium 'OH + H, PO, e H 2 0 + H2PO', were evaluated as 4.2 x lo4 and 2.5 x lo3 dm3 mol-' s-' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 18 publications
3
34
1
2
Order By: Relevance
“…This indicates an increase in the oxidant potential upon protonation and this is consistent with the results observed in the voltammetric study. However, accurate values could not be found in the literature (rather some estimations of the values that confirm these observations [39]). …”
Section: Voltammetric Studymentioning
confidence: 52%
See 2 more Smart Citations
“…This indicates an increase in the oxidant potential upon protonation and this is consistent with the results observed in the voltammetric study. However, accurate values could not be found in the literature (rather some estimations of the values that confirm these observations [39]). …”
Section: Voltammetric Studymentioning
confidence: 52%
“…According to the literature [39,40], the reduction potentials of these phosphate radicals can differ significantly and it has been reported that (PO 4 2-) Á oxidizes I -rapidly, (HPO 4 -) Á can also oxidize Br -and (H 2 PO 4 ) Á can even oxidize Cl -. This indicates an increase in the oxidant potential upon protonation and this is consistent with the results observed in the voltammetric study.…”
Section: Voltammetric Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The later combination of peroxophosphate radicals allows the production of the more stable peroxodiphosphate anion (Eq. 2) [36].…”
Section: Resultsmentioning
confidence: 98%
“…As compared with carbonate or hydrocarbonate ions the reactivity of sulfate or hydrosulfate anions is rather different (Jiang et al, 1992 …”
Section: Radiolysis Of Aqueous Solutions Relevant To Nuclear Waste Prmentioning
confidence: 99%